Edukasi Skincare Bebas Merkuri sebagai Upaya Peningkatan Literasi Keamanan Kosmetik pada Siswa SMKN 1 Boalemo - Netty Ino Ischak; Najmah Najmah; Deasy Natalie Botutihe (-, 2026)
The use of skincare products among teenagers is increasing alongside the growing trend of beauty, the influence of social media, and the need to maintain appearance and skin health. However, the high level of interest among teenagers in skincare is not always accompanied by adequate knowledge of cosmetic safety, particularly in identifying products containing harmful ingredients such as mercury. The purpose of this community service activity is to raise awareness of safe and mercury-free skincare products through education on cosmetic safety. The target audience for the activity is 32 SMKN 1 Boalemo students. The method of implementation involves the delivery of materials by the speaker on the subject of skincare for teenagers that is free of mercury, the dangers of mercury to health, the importance of BPOM approval, reading product labels, and critical thinking about cosmetic claims. The activity continued with a question-and-answer session and a practical demonstration through a video of cosmetics containing mercury and their impact on health. The results of the activity show that education on mercury-free skincare contributes to increasing students’ knowledge and understanding regarding the importance of choosing skincare products that are safe, legal,suited to their skin’s needs, and not easily swayed by viral products or claims of rapid skin whitening. Visual media, such as informational materials and practical demonstration videos, helped participants understand the risks of mercury-containing cosmetics in a more concrete way. This activity serves as a preventive measure to shape high school students into more critical, informed, and responsible teenage consumers when using skincare products. Thus, mercury-free skincare education is essential in school settings to strengthen cosmetic safety literacy from a young age.